Model risk: illuminating the black box. (2018) - Black, R.; Tsanakas, A.; Smith, A. D.; Beck, M. B.; Maclugash, I. D.; Grewal, J.; Witts, L.; Morjaria, N.; Green, R. J.; Lim, Z.
Abstract: This paper presents latest thinking from the Institute and Faculty of Actuaries' Model Risk Working Party and follows on from their Phase I work, Model Risk: Daring to Open the Black Box . This is a more practical paper and presents the contributors' experiences of model risk gained from a wide range of financial and non-financial organisations with suggestions for good practice and proven methods to reduce model risk. After a recap of the Phase I work, examples of model risk communication are given covering communication: to the Board; to the regulator; and to external stakeholders. We present a practical framework for model risk management and quantification with examples of the key actors, processes and cultural challenge. Lessons learned are then presented from other industries that make extensive use of models and include the weather forecasting, software and aerospace industries. Finally, a series of case studies in practical model risk management and mitigation are presented from the contributors' own experiences covering primarily financial services.